The complexity of online collaborative writing - Paiva, Vera Lucia Menezes de Oliveira e (Revista Horizontes de Linguistica Aplicada, 2015)
Abstract This paper focuses on collaboration, collective intelligence, and wiki technology in a complex perspective. It presents some results from qualitative research carried out with Brazilian university students using wiki tools to write collaborative essays. The results demonstrate that the use of wiki did not change the behavior of the majority of participants because they resisted collaboration, which is considered an essential element for the dynamicity of a complex learning system. Keywords: dynamic systems,collaboration, wiki. Resumo Este trabalho foca a colaboração, a inteligência coletiva e a tecnologia wiki em uma perspectiva complexa. Apresenta resultados de uma pesquisa qualitativa com alunos universitários brasileiros, usando ferramentas wiki para escrita de textos de forma colaborativa. Os resultados demonstram que o uso de wiki não mudou o comportamento da maioria dos participantes porque eles resistiram Ã  colaboração que é um elemento essencial para um sistema de aprendizagem complexo e dinâmico. Palavras-chave: sistemas dinâmicos, colaboração, wiki.